2021
DOI: 10.7759/cureus.20197
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy Among the Adult Population in Saudi Arabia

Abstract: Background: Vaccine hesitancy in Saudi Arabia continues even after reaching 17 million doses. This study was conducted to comprehensively assess coronavirus disease 2019 (COVID-19) vaccine hesitancy in adult people who ignore the COVID-19 vaccine in the Saudi Arabian population and explore community awareness of public health after 17 million doses of COVID-19 vaccination.Methods: A cross-sectional survey was used in this study. The questionnaire included three domains: demographic information, vaccine hesitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Certain sociodemographic variables were associated with vaccine acceptance (p < 0.05), including being male (n = 15), 14 15-18 22-24 25-28 29-34 39-40 44 being younger (n = 5), 18 , 22 , 24 , 32 , 39 and being married (n = 3). 17 , 27 , 40 Other predictors of vaccine acceptance were positive behavior regarding the influenza vaccine or vaccines in general (n = 12), 14 , 15 , 19 , 20 , 22 , 23 , 26 , 29 , 33 , 37 , 39 , 42 a high risk perception of contracting COVID-19 (n = 12), 14 15-18 21-22 25-27 28-36 38-42 trust in the government/healthcare system (n = 7), 17–25 27–33 37–43 a history of chronic illnesses (n = 4), 28 , 29 , 36 , 39 being a healthcare worker (n = 2), 14 , 23 and being a smoker (n = 2). 21 , 39 In one study, being female was associated with better knowledge of, attitudes toward, and perception of the vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Certain sociodemographic variables were associated with vaccine acceptance (p < 0.05), including being male (n = 15), 14 15-18 22-24 25-28 29-34 39-40 44 being younger (n = 5), 18 , 22 , 24 , 32 , 39 and being married (n = 3). 17 , 27 , 40 Other predictors of vaccine acceptance were positive behavior regarding the influenza vaccine or vaccines in general (n = 12), 14 , 15 , 19 , 20 , 22 , 23 , 26 , 29 , 33 , 37 , 39 , 42 a high risk perception of contracting COVID-19 (n = 12), 14 15-18 21-22 25-27 28-36 38-42 trust in the government/healthcare system (n = 7), 17–25 27–33 37–43 a history of chronic illnesses (n = 4), 28 , 29 , 36 , 39 being a healthcare worker (n = 2), 14 , 23 and being a smoker (n = 2). 21 , 39 In one study, being female was associated with better knowledge of, attitudes toward, and perception of the vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed in a review that the inclined awareness about safe vaccines and being honest in reporting adverse effects could help in tackling the delay faced in vaccine acceptance and improving the uptake of immunization. 13 …”
Section: Introductionmentioning
confidence: 99%
“…It was revealed in a review that the inclined awareness about safe vaccines and being honest in reporting adverse effects could help in tackling the delay faced in vaccine acceptance and improving the uptake of immunization. 13 Several studies from various other areas of the world reported fewer side effects after administrating the first or second dose, such as pain at the site of injection, swelling, tenderness, redness, warmth, itch, and swollen armpit glands, headache, fever, fatigue, night sweats, chills and shivering, joint pain, muscle pain, nausea, vomiting, and loss of appetite. [14][15][16][17][18][19] Despite the reality that the clinical studies assured the vaccine was safe and effective, it had limitations, such as a few participants recruited in the clinical studies and a healthier than real-world sample.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study conducted in various primary healthcare facilities in the capital city of Saudi Arabia demonstrated that, many people lack awareness of the influenza virus and its vaccine, hold strong misconceptions about side effects and believe it is useless [6,7]. A cross-sectional survey in Saudi Arabia reported that 82% of the respondents, who were adults, prefer to take precautions against the COVID-19 infection rather than take the vaccine [8].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in the western countries, the factors that predict caregivers' readiness to vaccinate children in the age group [5][6][7][8][9][10][11]…”
Section: Introductionmentioning
confidence: 99%